2020
DOI: 10.1021/acs.chemrestox.9b00442
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Chemical Characterization of the Aerosol Emissions of a Vaping Product Based on a New Technology

Abstract: Around 10 million people in the United States and 3 million people in the United Kingdom are estimated to use vaping category products. There are some estimates that there will be 75−80 million vapers worldwide by 2020. Most of these products are based on coil-and-wick technology. Because the heating and aerosol formation are separate processes, the system can lead to dry-wicking and elevated emission of carbonyls if designed and/or manufactured poorly. Low-nicotine and low-power coiland-wick devices have also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 41 publications
0
28
0
1
Order By: Relevance
“…The IS1.0(TT) e-cig uses a novel distiller plate technology to generate and deliver an e-cig aerosol. Analytical assessment of the respective aerosol emissions has shown that the IS1.0(TT) e-cig aerosol contains significantly reduced levels of known toxicants, and in many cases the toxicant levels were below the levels of detection for the analytical test methods [ 17 ]. The same study also showed that IS1.0(TT) emissions contained lower levels of toxicants than those from a comparator e-cig based on coil-and-wick technology.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The IS1.0(TT) e-cig uses a novel distiller plate technology to generate and deliver an e-cig aerosol. Analytical assessment of the respective aerosol emissions has shown that the IS1.0(TT) e-cig aerosol contains significantly reduced levels of known toxicants, and in many cases the toxicant levels were below the levels of detection for the analytical test methods [ 17 ]. The same study also showed that IS1.0(TT) emissions contained lower levels of toxicants than those from a comparator e-cig based on coil-and-wick technology.…”
Section: Discussionmentioning
confidence: 99%
“…That the aerosol from the IS1.0(TT) e-cig had levels of known toxicants that were either substantially reduced or absent is directly reflected in the corresponding lack of biological activity that we observed. Indeed, the distiller plate technology employed by this device delivers even lower levels of toxicants than a conventional coil and wick-based e-cig [ 17 ]. IS1.0(TT) was not compared with a coil and wick-based e-cig directly in the current toxicological evaluation study, and so a direct comparison of in vitro data with the aerosol emission data is not possible in this instance.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…1). For the ECs, considering the yields published (Margham et al 2016;Nicol et al, 2020) for the 21 selected compounds, the calculated mean lifetime cancer risk was respectively 2.42•10 -4 and 3.95•10 -4 . As these values are representative of two products only, no statistical analysis was performed, and they were plotted as single points on Fig.…”
Section: Cancer Potency and Mean Lifetime Cancer Riskmentioning
confidence: 99%